Praktikalitas E-Modul: Sinergi Nilai Karakter dan Kearifan Lokal untuk Menguatkan Karakter Mahasiswa Menuju Era Society 5.0 - Rahmadani, Ervi; K, Nurdin; Irfandi; Susianti, Susianti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to examine the practicality of e-modules of Character Education Characterized by Local Wisdom. This research is follow-up research from previous research. This research is quantitative research using an instrument in the form of a practicality questionnaire totaling 15. The focus of the practicality test is the efficiency of the e-module, the benefits and ease of use. The data that has been obtained, then each is analyzed for each indicator in the form of a percentage, both from the responses of lecturers and students. Respondents consisted of students and lecturers totaling 106 people within the scope of the Faculty of Education and Teaching Training of the Islamic Education Management Study Program. The average response from lecturers was 90% which was included in the very practical category and the response from students was 83.5% which was included in the practical category. In addition, researchers also made improvements and several revisions for the convenience of users including adding images and layouts, until finally this e-module was completed in its development stage and could be used as teaching material in the lecture process in the Character Education course.